2018
DOI: 10.1038/nrneph.2017.167
|View full text |Cite
|
Sign up to set email alerts
|

Genomic medicine for kidney disease

Abstract: Technologies such as next-generation sequencing and chromosomal microarray have advanced the understanding of the molecular pathogenesis of a variety of renal disorders. Genetic findings are increasingly used to inform the clinical management of many nephropathies, enabling targeted disease surveillance, choice of therapy, and family counselling. Genetic analysis has excellent diagnostic utility in paediatric nephrology, as illustrated by sequencing studies of patients with congenital anomalies of the kidney a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 285 publications
(326 reference statements)
0
123
0
1
Order By: Relevance
“…One possible reason for the low detection rate of CMA in CAKUT is that many CAKUT cases were caused by a single gene defect. Up to now, more than 200 monogenic syndromes have been described involving renal or urinary anomalies as one of their features . In one recent study performed by Lei et al, pathogenic variants were identified through whole exome sequencing (WES) in four of 30 fetuses with CAKUT, despite normal findings upon karyotyping and CMA, indicating that WES may further improve the diagnostic rates of CAKUT in prenatal cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason for the low detection rate of CMA in CAKUT is that many CAKUT cases were caused by a single gene defect. Up to now, more than 200 monogenic syndromes have been described involving renal or urinary anomalies as one of their features . In one recent study performed by Lei et al, pathogenic variants were identified through whole exome sequencing (WES) in four of 30 fetuses with CAKUT, despite normal findings upon karyotyping and CMA, indicating that WES may further improve the diagnostic rates of CAKUT in prenatal cases.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the underlying genetic etiology of CAKUT may improve prenatal diagnosis, genetic counseling, and clinical management. Chromosomal microarray analysis (CMA) has been successfully applied to the identification of copy number variations (CNVs) in pediatric nephropathy and has been shown to be an effective first‐line diagnostic tool in patients with CAKUT . Previous studies have demonstrated that CMA can detect pathogenic CNVs in 4% to 10% of postnatal patients with CAKUT, a diagnostic yield comparable with that noted for the established indications of developmental delay .…”
Section: Introductionmentioning
confidence: 99%
“…NGS panel tests to target a pre‐determined set of genes and detect single‐nucleotide variants (SNV) and small insertions or deletions (indels). Targeted testing reduces the risk of incidental findings; however, it relies on the correct gene panel being selected, and the panel content being regularly updated in light of new gene discoveries . In 2013, an expert team of nephrologists, clinical geneticists and molecular geneticists developed an exome‐based panel approach to provide a comprehensive national diagnostic service in Australia.…”
Section: Genomic Sequencing As a Diagnostic Testmentioning
confidence: 99%
“…Patients should be referred for genetic or genomic testing if it is necessary to confirm a suspected genetic diagnosis, or to clarify or exclude other differential diagnoses . A definitive diagnosis may negate the need for prolonged diagnostic investigations and surveillance . In addition, it may provide prognostic information, including informing targeted surveillance of extra‐renal manifestations .…”
Section: Who Should Be Referred For Genetic/genomic Testing?mentioning
confidence: 99%
See 1 more Smart Citation